THE ROLE OF SUSTAINABLE DEVELOPMENT CONCEPTS IN TEACHING THE SUBJECT OF BIOGENIC ELEMENTS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
The following article discusses the role and importance of the concept of sustainable development in teaching the topic of biogenic elements in the 8th chemistry lesson. It is not surprising that this article is a solution to some of the current problems